Shaping a future of painting: the early Neolithic pottery from Dzhulyunitsa, North Central Bulgaria - Dzhanfezova, T; Doherty, C; Elenski, N (Association of Bulgarian Archaeologists, 2014)
This paper presents the somewhat unexpected findings of a preliminary archaeometric study of ‘painted’ early Neolithic pottery from the site of Dzhulyunitsa, north central Bulgaria. While there is still no consensus on the actual model of Neolithisation of this region, expectations are that there would have been a transfer of pottery technology and possible small quantities of painted pottery from the West Anatolian homeland to early Neolithic sites in Bulgaria. However, our findings confound these expectations. Pottery from the earliest levels of the site are all based on local materials: there are no imported wares. There is no evidence of the experimental phase that would be expected as migrant potters learned to adjust to local clays. Instead the pottery is of a very high quality from the outset, using naturally fine clays that do not require temper: though organic material is sometimes added, albeit often in non-functional quantities. What were thought to be dark-painted layers are shown to be simply the high-quality burnishes that can be developed using these micaceous local clays: in some cases with outer surfaces enhanced with ochre. White-slipped and white-on red decorated sherds from the second layer of the site continue to showcase a mastery of local materials, with white pigments base on nearby limestones and marls. But here, petrographic analysis identifies some white-painted wares which are clearly not local, with both bodies and paint compositions pointing to a different provenance and technology. As it continues, this project aims to establish the full range of Dzhulyunitsa pottery fabrics to reconstruct manufacturing technologies and raw material sourcing patterns, for comparison with contemporary sites across the region.